It could happen here : why America is tipping from hate to the unthinkable--and how we can stop it - Greenblatt, Jonathan (Mariner Books, an imprint of HarperCollinsPublishers, 2022)
"From the dynamic head of Anti-Defamation League (ADL), an impassioned argument about the terrifying path that America finds itself on today--and how we can save ourselves"--Flap page 1 of dust jacket.